Performance of small basis set Hartree–Fock methods for modeling non-covalent interactions. (20th September 2021) - Prasad, Viki Kumar; Otero-de-la-Roza, Alberto; DiLabio, Gino A
Abstract: Non-covalent interactions (NCIs) play an essential role in (bio)chemistry. Wavefunction-based methods combined with large basis sets are able to accurately describe inter-and intra-molecular NCIs but are not practical for large molecular systems. Semi-empirical corrections have been developed recently that, when combined with Hartree–Fock (HF) and a small basis set, show promise in the ability to predict non-covalent binding and conformational energies over a wide range of systems. Compared to large-basis-set correlated wavefunction methods, small-basis-set HF methods significantly lower computational cost and are useful for modeling large molecular systems with sizes between many hundreds and a few thousand atoms. Using a large collection of non-covalent binding energies, conformational energies, and molecular deformation energies containing 105 880 entries, we provide a comprehensive evaluation of the performance of the minimal basis set (MINIX) HF method with three correction schemes: D3, 3c, and atom-centered potentials (ACPs). We also evaluate the performance of HF/6-31G* in combination with the D3 and ACP schemes. By comparing the three corrections, we analyze the strengths and weaknesses associated with each strategy in predicting NCIs. Our results show that D3 corrections alone do not offer significant improvements in the performance of HF/MINIX or HF/6-31G* and, in some cases, overestimate binding energies resulting in large errors when compared to the reference data. The correction strategies that offer the best reduction in the underlying errors of HF/MINIX and HF/6-31G* are shown to be 3c and ACP for HF/MINIX and ACP for HF/6-31G*.